2021
DOI: 10.1016/j.eucr.2021.101806
|View full text |Cite
|
Sign up to set email alerts
|

Intraabdominal mass in adult men with unilateral UDT revealed as seminoma: A case report

Abstract: Undescended testis is most common congenital malformation in boys. Most common location is inguinal canal but rarely it is found in intraabdominal. 10% of them will grow become mass if left untreated. This case report describes cases of men of 40s with unilateral UDT and not noticeable until they felt heavy and feel palpable mass in abdomen revealed as seminoma. He is sterile and not be able to reproduce. Chemotherapy was done and the response was remarkable. This case report reiterates the need for a scrotal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Studies have found that 20% of undescended testis were non-palpable, and 25%–40% were non-palpable intraabdominal testes ( 23 , 24 ).Undescended testis had an incidence of 1%–3% in full-term male newborns and about 0.8% at one year of life. It is estimated that undescended testis cause around 10% of all testicular tumors, with the risk being higher for testicles in the abdomen ( 25 ). However, the molecular mechanism behind the development of malignancy and failed testicular descent remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that 20% of undescended testis were non-palpable, and 25%–40% were non-palpable intraabdominal testes ( 23 , 24 ).Undescended testis had an incidence of 1%–3% in full-term male newborns and about 0.8% at one year of life. It is estimated that undescended testis cause around 10% of all testicular tumors, with the risk being higher for testicles in the abdomen ( 25 ). However, the molecular mechanism behind the development of malignancy and failed testicular descent remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…More rarely, renal pelvic dilation can occur due to compression from the primary tumor when it reaches a large size. 5 This rare presentation mode along with the imaging findings posed a differential diagnostic problem. Indeed, the possibility of left upper tract urothelial carcinoma could not be excluded especially when transitional cell carcinoma is endemic in our country.…”
Section: Discussionmentioning
confidence: 99%
“…If the patient does not mention the presence of an undescended testis, the scrotal test is easily omitted during physical examination. In fact, a previous study emphasized on the importance of conducting scrotal test in men with an abdominal mass to rule out intra-abdominal seminoma [6] .…”
Section: Discussionmentioning
confidence: 99%